CTGF as a multifunctional molecule for cartilage and a potential drug for osteoarthritis - Yang, Zihuan; Li, Weishi; Song, Chunli; Leng, Huijie (Frontiers in Endocrinology, 2022)
CTGF is a multifunctional protein and plays different roles in different cells and under different conditions. Pamrevlumab, a monoclonal antibody against CTGF, is an FDA approved drug for idiopathic pulmonary fibrosis (IPF) and Duchenne muscular dystrophy (DMD). Recent studies have shown that CTGF antibodies may potentially serve as a new drug for osteoarthritis (OA). Expression of CTGF is significantly higher in OA joints than in healthy counterparts. Increasing attention has been attracted due to its interesting roles in joint homeostasis. Joint homeostasis relies on normal cellular functions and cell-cell interactions. CTGF is essential for physiological activities of chondrocytes. Abnormal CTGF expression may cause cartilage degeneration. In this review, the physiological functions of CTGF in chondrocytes and related mechanisms are summarized. Changes in the related signaling pathways due to abnormal CTGF are discussed, which are contributing factors to inflammation, cartilage degeneration and synovial fibrosis in OA. The possibility of CTGF as a potential therapeutic target for OA treatment are reviewed.